Evaluating the Changing Comparative Advantage Patterns and Export Specialization of East Java province (Indonesia) - Padilla, Miguel angel esquivias (Universitas Airlangga, 2016)
East Java (JATIM), the second largest province in Indonesia in terms of population and GDP contribution had experienced 50 percent of export growth from 2007 to 2013. The changes were not only in value but in composition and destination, meaning that a change in the pattern of exports of JATIM and export performance was observed in the seven years of analysis. This study looks at those changes from the point of view of comparative advantage and export specialization. JATIM kept 55 percent of their competitive industries since 2007 as the backbone of their exports, losing the other 45 percent, while allowing the creation of new industries. The gains in new industries are higher than the losses indicating that relocation of resources and the change of focus is bringing benefits to the province. Dynamic changes had occurred among commodities –gains and losses in comparative advantage and export specialization-, some presumed to be driven by commodity prices while others are more related to global integration.